Seven problems with the “scarce skills” discourse in South Africa - Balwanz, D; Ngcwangu, S (South African Journal of Higher Education, 2016)
The concept of “scarce skills” features prominently in South Africa’s national development discourse. Over the past decade, the “scarce skills” concept has been used to frame debate about the relationship between post-school education and training and the economy. In this article, we compare education policy documents articulating “scarce skills” perspectives with plans from four occupational sectors and general labour market data and analysis. In our analysis, we identify ideological, theoretical, conceptual and methodological limitations to the “scarce skills” discourse. Each limitation contributes to a reduced and myopic understanding of the complex and dynamic relationship between post-school education and the economy. We conclude by sharing three arguments which post-school institutions could draw on to respond to the skills discourse.